Attacking and defensive styles of play in elite soccer - Fernandez Navarro, J.; Ford, P. R.; Scott, M.; Fradua, L.; Zubillaga, A.; McRobert, A. P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Soccer teams use different styles of play or strategies in competition (Tenga et al., 2003). However, performance indicators associated with attacking and defending styles of play have not been clearly defined. The aim of this study was to use factor analysis to define and categorise the different styles of play used in elite soccer and determine the performance indicators that contribute to them. Methods: Ninety-seven matches, involving 37 different teams from 1st Spanish La Liga and the English Premier League (2006-2007 and 2010-2011) were monitored using a multiple-camera match analysis system (Amisco Pro®, version 1.0.2, Nice, France). Nineteen attacking (1) and defending (5) performance indicators were measured. Factor analysis using principal component analysis (PCA) was conducted on the 19 performance indicators with orthogonal rotation (varimax). This technique allows the grouping of performance indicators into a few factors that represent the styles of play. In addition, each team`s specific way of playing can be categorised by describing their score for each factor. Results: The Kaiser-Meyer-Olkin measure verified the sampling adequacy for the analysis (KMO = .53). Six factors extracted in the factor analysis explained 84.91% of the variance. Factor 1 explained the largest variance (27.8%). Two opposing styles of play were associated with each factor based on a positive or negative score. The attacking styles of play determined were: direct or possession, crossing or no crossing, wide possession or narrow possession, and fast progression of possession or slow progression of possession. In contrast, the defensive styles of play were: applying pressure/regaining the ball in wide areas or applying pressure/regaining the ball in central areas, and low pressure or high pressure. The six factors described 12 different ways that teams played (8 attacking and 4 defending). Discussion: Factor analysis revealed the different styles of play used in elite soccer and the performance indicators that contribute to them. A team`s score on each factor demonstrated their dependence on a style of play (Pollard et al., 1988). For example, one English team`s way of playing was to use the direct, no crossing, narrow and fast progression styles of play in attack. In defence they used a low pressure but applied pressure in central areas to regain the ball. The implications are that training can be designed to improve the performance indicators associated with the team`s styles of play or prepare them to face the styles of play of upcoming opponent`s.